Risk of Cardiac Adverse Events in Patients Treated With Immune Checkpoint Inhibitor Regimens: A Systematic Review and Meta-Analysis - Hu, Jiexuan; Tian, Ruyue; Ma, Yingjie; Zhen, Hongchao; Ma, Xiao; Su, Qiang; Cao, Bangwei (Frontiers in Oncology, 2021)
Abstract： Background: We performed a systematic review and meta-analysis to evaluate the risks of cardiac adverse events associated with treating solid tumor patients using PD-1/PD-L1 inhibitor monotherapy or PD-1/PD-L1 inhibitor plus chemotherapy. Methods: Eligible studies were selected through the following databases: PubMed, Embase and clinicaltrials (https:// clinicaltrials.gov.) and included phase III/IV randomized controlled trials (RCTs) investigating ICIs in patients with the solid tumor.The data was analyzed by using Review Manager (version5.3), Stata (version 15.1). Results: Among 2551 studies,We identified 25 clinical trials including 20244 patients that were qualified for the meta-analysis. Compared with PD-1 inhibitor(nivolumab) or CTLA-4 inhibitor(ipilimumab),PD-1 inhibitor(nivolumab) plus CTLA-4 inhibitor(ipilimumab) combined therapies showed significant increase in grade 5 arrhythmology (OR 3.90,95% CI:1.08-14.06, p=0.603).PD-1 inhibitor plus chemotherapy show significant increase in grade 1–5 myocardial disease(OR 5.09,95% CI:1.11-23.32,p=1.000).Compared with chemotherapy,PD-1 inhibitor(nivolumab) or CTLA-4 inhibitor(ipilimumab), PD-1 inhibitor(nivolumab) plus CTLA-4 inhibitor(ipilimumab) combination therapies show significant increase in grade 1-5 arrhythmology(OR 2.49,95% CI:1.30-4.78, p=0.289). Conclusions:Our meta-analysis demonstrated that PD-1 inhibitor plus CTLA-4 inhibitor can result in a higher risk of grade 5 arrhythmology in comparison with PD-1/CTLA-4 inhibitor and can result in a higher risk of grade 5 arrhythmology in comparison with chemotherapy. PD-1 inhibitor plus chemotherapy treatment could increase the risk of all-grade myocardial disease compared with chemotherapy.However, most of the time there was no significant increase of risk of Cardiovascular toxicity no matter PD-1/PD-L1 inhibitor monotherapy or PD-1/PD-L1 inhibitor plus chemotherapy compared with chemotherapy alone.